The optimal true-ileal-digestible lysine and total sulfur amino acid requirement for finishing pigs fed paylean® - N Z Frantz; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 1887 pigs (PIC 337 × C22; 213 lb initial BW) were used in a 28-d growth assay to simultaneously examine both the true-ileal-digestible (TID) lysine and TID total sulfur amino acid (TSAA) requirements. The objective was to determine the appropriate TID TSAA-to-lysine ratio in finishing pigs fed PayleanÂ® (4.5 g/ton) to maximize growth performance and carcass composition. Four TID lysine (0.66. 0.79, 0.92, and 1.05%) and four TID TSAA (0.47, 0.52, 0.57, and 0.63%) concentrations were evaluated. The highest lysine and TSAA concentrations were combined in the same diet, and there were eleven or twelve replicate pens per treatment. The lysine treatments were formulated with a minimum TID TSAA to lysine ratio of 60%, and the TSAA diets were formulated with 1.05% TID lysine. No gender × treatment or treatment × week interactions were observed (P>0.13). Increasing TID lysine increased ADG (linear, P0.76) was not affected by increasing TID TSAA. This resulted in a TID TSAA-to-lysine ratio of not more than 51% for optimum ADG. Increasing TID lysine did not affect ADFI (P>0.60), but ADFI decreased (linear, P0.11), but increasing TID TSAA from 0.47 to 0.52% tended to improve fat-free lean (quadratic, P0.10). In summary, a TID TSAA-to-lysine ratio of 58% optimizes growth performance of finishing pigs fed Paylean.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Finishing pigs; Lysine; Methionine; Paylean; Pigs; Sulfur amino acids; Swine